SOCIAL SOLIDARITY IN MULTICULTURAL EDUCATION AS NATION’S IDENTITY - Yudi Pratama (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This article see the lack of solidarity in Indonesia. This issue is indicated from a big numberof conflicts emerged in the country with the factor of race and religion. As what EmileDurkheim said about solidarity, that it is something indicating the relationship amongindividual and groups based on emotional morality and trust which are shared together.Social solidarity is emerged not only on society with shared background among themembers but also one with different background. The difference of the background had bythe members of society will trigger the emergence of social harmony as well as solidarity.To make the condition stated happened, the most effective way of doing it is via education.Through which the value of character education can be inserted. Seeing from the variedcultures in Indonesia, it is the most suitable way to create social solidarity. By doing this,the Indonesians can appreciate the differences so there will be harmonic life created inIndonesia.Keywords: Social solidarity, Multicultural Education, National Identity